The Role of Teacher-Librarian in Building Lifelong Learning for Students - Hendro Margono; Nadya Ananda Tri Anugrah Putri (UPT Perpustakaan UIN Alauddin Makassar, 2023)
Teacher Librarian is usually a teacher who also acts or is responsible as a librarian in the school library. Teachers who have a minimum education in the field of library science Diploma two (D-II) at an accredited university or complete a minimum Diploma two (D-II) education which is then continued with training and learning in the library field. However, in Indonesia there is often a phenomenon of teacher-librarians who do not have scientific provision in the library field so that in some cases in real life, the management of the library system becomes less than optimal and cannot be utilized by users properly. In contrast to other countries, it is known that many schools in Europe use teacher-librarians as school library staff. This is so that teacher-librarians can collaborate with teachers to improve the quality of learning as well as the literacy skills of their students. School libraries should also have interesting and effective programs because this can affect students' learning achievement. Lifelong Learning is learning that is carried out throughout life without coercion on one's part to improve their abilities and knowledge so that they can create good competitiveness for their environment. Students who act as lifelong learners need proper guidance, namely with the help of Teacher-Librarians and also teaching teachers during the learning process. This article uses a literature review method that critically reviews ideas or findings in academically oriented literature.